Studie av USA och EU:s utrikespolitiska agerande gentemot Hamas - Kan den strukturella realismen förklara aktörernas agerande? - Arnell,Adam (2015)
In this comparative study I’ve chosen to look at the foreign policies underlying the statements made by the U.S. and EU directed against Hamas. The U.S. and EU cooperate on a higher level than expected in the difficulties surrounding Hamas and the Israeli-Palestinian conflict in general, and their cooperation is mainly represented by the Quartet of the Middle East and its work. The Quartet is the central player in the difficulties surrounding Hamas and it’s working to mediate and promote a democratization process in Palestine. Structural realism has been applied and used for a theory-testing analysis of the U.S. and EU actions. The aim was to test whether the structural realism could explain the U.S. and EU actions against Hamas. Structural realism gave in this study a weak and unsuccessful interpretation and explanation of how and why the U.S. acted as they did. The case with EU on other hand, made structural realism a bit more relevant and gave a weak, but better explanation to why EU acted as they did.
Keywords: The U.S; EU; Hamas; Foreign Policy; structural realism; the Quartet of the Middle East